Market power in CEE banking sectors and the impact of the global financial crisis - Georgios Efthyvoulou; Canan Yildirim (Center for Social and Economic Research (CASE), 2013)
The aim of this study is to undertake an up-to-date assessment of market power in Central and Eastern European banking markets and explore how the global financial crisis has affected market power and what has been the impact of foreign ownership. Three main results emerge. First, while there is some convergence in country-level market power during the pre-crisis period, the onset of the global crisis has put an end to this process. Second, bank-level market power appears to vary significantly with respect to ownership characteristics. Third, asset quality and capitalization affect differently the margins in the pre-crisis and crisis periods. While in the pre-crisis period the impacts are similar for all banks regardless of ownership status, in the crisis period non-performing loans have a negative effect and capitalization a positive effect only for domestically-owned banks.
Keywords: F23; G01; G21; L10; 330; bank market power; CE European countries; global financial crisis; foreign ownership; Marktmacht; Bank; Eigentümerstruktur; Finanzkrise; Osteuropa